Enzymatic pathway for kupyaphore degradation in mycobacterium tuberculosis: mechanism of metal homeostasis and turnover - Bhosale, Rashmi S.; Chakraborty, Arnab; Wong, Tsung-Yun; Masal, Dattatraya P.; Choudhury, Rahul; Srivastava, Sonali; Reddy, D. Srinivasa; Aldrich, Courtney C.; Kamat, Siddhesh S.; Mohanty, Debasisa; Gokhale, Rajesh S. (ACS Chemical Biology, 2025)
Metallophores are essential for metal homeostasis, regulating availability, and mediating host-pathogen interactions. Kupyaphores are specialized metallophores produced by Mycobacterium tuberculosis (Mtb) that primarily chelate zinc to support bacterial survival. Elevated kupyaphore levels early in infection highlight their importance, while their rapid decline, despite increasing bacterial loads, indicates tightly regulated mechanisms of production, consumption, and degradation. However, the processes driving kupyaphore catabolism and their role in preventing zinc toxicity in Mtb remain unclear. Here, we show that covalent modification of the isonitrile moiety in kupyaphores releases zinc, triggering degradation through a sequential three-step enzymatic pathway encoded by Mtb. Isonitrile hydratase converts isonitrile groups into formamides, which are subsequently processed into amines by N-substituted formamide deformylase and ultimately oxidized to beta-ketoesters by amine oxidases. The biological significance of this pathway is underscored by the upregulation of these genes under metal-depleted and biofilm-forming conditions. Mutant Mtb strains lacking these genes exhibit impaired growth in metal-limiting environments and reduced levels of biofilm formation. Catalytic intermediates detected in Mtb cultures and infected mouse lung tissues confirm the pathway's in vivo activity. Further, genome mining reveals that similar enzymes are conserved across organisms producing isonitrile-containing metabolites, emphasizing the broader importance of this pathway. Understanding these processes could pave the way for novel therapeutic strategies targeting kupyaphore catabolism.

Novel routes for bioproduction of delta lactone aroma compounds - Srivastava, Sonali; Chandramouli, Aakash; Gupta, Payal; Manzer, Abdur Rahman; Choudhury, Rahul; Reddy, D. Srinivasa; Yazdani, Syed Shams; Kamat, Siddhesh S.; Mohanty, Debasisa; Nandicoori, Vinay K.; Gokhale, Rajesh S. (Metabolic Engineering, 2026)
Delta lactones are fatty acid-derived aroma compounds that hold tremendous commercial value. As consumer demand for natural flavours continues to rise, the bioproduction of S-lactones, including S-decalactone and S-dodecalactone, is attracting substantial interest. Our study brings forth a novel approach to the bioproduction of S-lactones from glucose, deviating from existing methods that primarily rely on the biotransformation of fatty acids. The high cost of fatty acid raw material constrains the commercial viability of this traditional approach. We engineered surface-lipid producing type I polyketide synthase (PKS) from Mycobacterium smegmatis by incorporating macrolactone thioesterase (TE) domain. Two out of three fusion constructs produced an appropriately engineered PKS-TE fusion protein that facilitated the synthesis of S-lactones. When grown on glucose as the sole carbon source, recombinant E. coli expressing the engineered PKS-TE fusion protein successfully made S-lactones ranging from C8-C18 acyl chains. Our research further highlights the potential of Mycobacterium smegmatis as a cell factory for producing fatty acid-based S-lactones. By genetically designing and engineering Mycobacterium smegmatis to express PKS-TE fusion protein, we achieved bioproduction of various S-lactones. Batch fermentation of the engineered E. coli strain fed with 2 % glucose produced 786 mg/L of S-dodecalactone and 444 mg/L of S-decalactone at 120 h, underscoring the efficacy of our approach. Thus, this study is the first to demonstrate a methodology for redirecting primary metabolic intermediates towards S-lactone biosynthesis in engineered bacteria, enabling the use of inexpensive and renewable feedstocks.
Keywords: Natural flavour; PKS engineering; S-decalactone; S-dodecalactone; S-lactone